Pengaruh Limbah Pasar Ikan Terhadap Status Mutu dan Daya Tampung Beban Pencemaran Sungai di Kecamatan Singkawang Barat - Julia, Julia; Kadaria, Ulli; Desmaiani, Herda (Universitas Tanjungpura, 2025)
Pasar Ikan Bersih in Singkawang is a fish market located on GM Situt Street, West Singkawang District. The fish market activities produce waste water from the remaining fish washing which is directly dumped into the river. This activity causes a decrease in the quality of river water around the fish market. The study was conducted to determine the water quality, water quality status using the pollutant index method and the pollution load capacity using the Streeter Phelps. The parameters to be studied are temperature, pH, DO, BOD, COD, and TSS. Parameters such as temperature, pH, and DO are analyzed manually.on site, while other parameters were analyzed in the laboratory. The results obtained from the water quality analysis were that there were several parameters that exceeded the quality standards of class II PP No. 22 of 2021, namely DO, BOD, and COD. In addition, the results obtained from the analysis of water quality status showed that the river was classified as lightly polluted with a value range of 2.36 - 3.44. From these calculations, it shows that the river in Singkawang is able to accommodate a pollution load of 2189.18 kg/day.